Islam and the veil: theoretical and regional contexts - Gabriel, Theodore; Gabriel, Theodore; Hannan, Rabiha (Continuum, 2011)
This volume is centred around the theme of veiling in Islam and provides multifarious aspects of the discussion regarding veiling of Muslim women, especially in the West. The issue of veiling has been intensively debated in Western society and has implications for religious liberty, inter-communal relationships and cultural interaction. Islam and the Veil seeks to generate open and objective discussion of this highly important, though controversial, subject, with contributions from distinguished scholars and academics, including female practitioners of Islam. This subject has inflamed passions and generated heated debate in the media in recent years, particularly in the West. This book aims to look at the historical background, theological and social factors underlying the veiling of women in Islam. Such discussion will provide the reader with a well-balanced and unbiased analysis of this important aspect of Islamic practice. -- Back cover